Meningkatkan Hasil Belajar IPA Materi Pesawat Sederhana melalui Model Pembelajaran Children Learning in Science - Irlismiarti (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2021)
The low learning outcomes of students in fifth grade SD Negeri 009 Singkep Barat on science subjects on simple machines highlight the importance of this classroom action research. This Classroom Action Research aims to improve the learning outcomes of fifth grade students, SD Negeri 009 Singkep Barat, in science learning through the Children Learning in Science (CLIS) learning model. This research uses classroom action research (CAR) that was carried out in two cycles. Each cycle has two meetings. The number of students is 22 students in fifth grade at SD Negeri 009 Singkep Barat. The research was conducted in the second semester of the 2019/2020 academic year. The results showed that using the Children Learning in Science (CLIS) learning model could improve student learning outcomes. The number of students who finished studying individually increased dramatically from cycle 1, as many as 16 (73%), in cycle II to 22 (100%) and the class average value in pre-cycle 64.54 to 71.36 in cycle I continued to increase in cycle II to 79.09. Classically, in the second cycle, the completeness of class learning has reached 100%. Therefore, this study concludes that the use of the Children Learning in Science (CLIS) learning model can improve students' learning outcomes for simple machine materials.